La Icnofacies Zoophycos-Chondrites del Cretácico de la Cordillera Occidental de Colombia y su posible significación paleoambiental La Icnofacies Zoophycos-Chondrites del Cretácico de la Cordillera Occidental de Colombia y su posible significación paleoambiental - Etayo Serna Fernando (Caldasia)
The Zoophycos-Chondrites ichnofacies is common in fine-grained Cretaceous sedimentary rocks, in both biosiliceous and terrigenous claystone and siltstone of the Western Cordillera of Colombia, but it is absent from isopic coeval rocks of the Central and Eastern Cordilleras: The absence of this ichnofacies is attributed to the influence of a belt of oceanic anoxic waters developped during middle and late Cretaceous, that caused stagnant episodes in the sea floor of the epicontinental seas that stretched across the places of the actual Central and Eastern Cordilleras, but that did not affect the deep-sea floor where the sediments of the present Western Cordillera were accumulating.  In sections perpendicular to the bedding the trace fossil Zoophycos generally appears as belt-like burrows composed of a series of closely juxtaposed meniscate markings. Identification in the axial vertical burrows of the concave-side of the menisci, that originally face up-section, may help as a way-up criterion when dealing with rocks affected by low-grade penetrative metamorphism. La icnofacies Zoophycos-Chondrites presente en sedimentitas finogranulares cretácicas de la cordillera Occidental de Colombia, no existe -hasta donde se conoce- en las rocas isópicas coetáneas de las cordilleras Central y Oriental. Esta falta de la icnofacies se explica si se tiene en cuenta que a mediados y finales del Cretácico hubo lapsos durante los cuales se generaron cinturones de aguas anóxicas, que tocaron los fondos finogranulares de los dominios del mar epicontinental que cubrió el centro y el oriente colombianos, mas no alcanzaron los fondos óptimos para el desarrollo de Zoophycos en el océano en el que se originó el actual occidente de Colombia.  La identificación de la posición de la concavidad de los meniscos semilunares de las galerías verticales axiales de Zoophycos, que miraron hacia la superficie de depósito, permite su utilización en el discernimiento de la polaridad estratigráfica en rocas afectadas por metamorfismo penetrativo de bajo grado.